Carbon-ion radiotherapy for patients with advanced stage non–small-cell lung cancer at multicenters. (14th July 2017) - Karube, Masataka; Yamamoto, Naoyoshi; Shioyama, Yoshiyuki; Saito, Junichi; Matsunobu, Akira; Okimoto, Tamaki; Ohno, Tatsuya; Tsuji, Hiroshi; Nakano, Takashi; Kamada, Tadashi
ABSTRACT: Carbon-ion radiation therapy (CIRT) for advanced non–small-cell lung cancer (NSCLC) has not been well studied to date. This paper aimed to analyze a retrospective multicenter survey for detecting problems with the use of CIRT for Stage II and III NSCLC (7th UICC TNM Staging System). Inclusion was restricted to patients with Stage II and III NSCLC who received CIRT from November 2003 to December 2014. We gathered the data from three CIRT operating centers on July 2015. Patients with radiotherapy history, patients with cancers other than lung cancer, and those receiving palliative therapies were excluded. The patient characteristics, prescribed dose/fraction, survival rates, and adverse effects were analyzed. The total number of patients was 64 (male: 49, female: 15). Of these, 53 patients were medically inoperable. The median age was 76 years (range 46–91), and the median follow-up period was 18.5 months (range 3.2–121.5). The clinical staging consisted of 10 Stage IIA, 30 Stage IIB, 23 Stage IIIA and 1 Stage IIIB. The median prescribed dose was 72.0 Gy (RBE) (range 52.8–72.0) in 16 fractions (range 4–16). The 2-year overall survival, progression-free survival, and local control rates were 62.2% [confidence interval (CI): 47.5–76.9], 42.3% (CI: 28.8–55.8) and 81.8% (CI: 69.9–94.0), respectively. There were no higher than Grade 2 adverse effects observed. CIRT for inoperable Stage II and III NSCLC could be implemented without severe adverse effects, but the clinical staging (including lymph node status) was inhomogeneous. In addition, the prescribed dose and fractionation were not standardized. Further data accumulation and a multiple centers prospective trial for evaluating clinical stage–based results are required.